Restoration of natural killer cell activity in chronic hepatitis C-infected Egyptian patients treated by sofosbuvir/daclatasvir with or without ribavirin - Hamdy M Moustafa; Muhammad Abdel-Gawad; Eman M Salaheldin; Nagat F.S Ibrahim (Wolters Kluwer Medknow Publications, 2021)
Background and aim Numerous studies demonstrate natural killer (NK) cell dysfunction in hepatitis C virus (HCV) infection. Direct-acting antivirals (DAAs) can change NK cell activation when HCV replication is inhibited. Only few studies have reported the effect of DAAs on NK cells, especially in genotype 4. Therefore, our study aimed to examine the effect of elimination of HCV by DAA therapy on NK activity in chronic hepatitis C-infected patients. Patients and methods A prospective cohort study was conducted on 50 Egyptian naïve chronic hepatitis C-infected patients. The patients were treated with sofosbuvir/daclatasvir±ribavirin for 12 weeks, and NK cells were detected at baseline and at 12 weeks after the end of the treatment by multicolor flow cytometry. Results Overall, 98% of studied patients achieved sustained virological response (SVR) 12. One patient did not achieve SVR 12; this patient was given a second course of treatment with sofosbuvir (ombitasvir/paritaprevir/ritonavir) and ribavirin for 12 weeks and successfully achieved SVR. Therefore, SVR 24 of studied patients was 100%, and there was a significant increase in cluster of differentiation 16+ cluster of differentiation 56+ after treatment compared with pretreatment data (P=0.000). Conclusion Elimination of HCV infection by DAA therapy can restore the frequency of NK cells of chronic hepatitis C-infected patients.